2017
DOI: 10.1128/iai.00173-17
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gamma Interferon- and Tumor Necrosis Factor Alpha-Driven Cytokine Response Distinguishes Acute Infection of a Metatherian Host with Toxoplasma gondii and Neospora caninum

Abstract: Toxoplasma gondii and Neospora caninum (both Apicomplexa) are closely related cyst-forming coccidian parasites that differ significantly in their host ranges and ability to cause disease. Unlike eutherian mammals, Australian marsupials (metatherian mammals) have long been thought to be highly susceptible to toxoplasmosis and neosporosis because of their historical isolation from the parasites. In this study, the carnivorous fat-tailed dunnart (Sminthopsis crassicaudata) was used as a disease model to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…Neosporosis often causes abortion especially in dairy cattle and leads to global economic losses ( 5 ); however, there is no treatment or vaccine available against this disease in cattle ( 6 ). Increasing attention has been paid to defining the role of the host immune response in N. caninum infection and to exploring the immune functions that influence control of infection and disease development ( 7 ). Host immune response against N. caninum infection is an essential determinant of neosporosis ( 1 , 6 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neosporosis often causes abortion especially in dairy cattle and leads to global economic losses ( 5 ); however, there is no treatment or vaccine available against this disease in cattle ( 6 ). Increasing attention has been paid to defining the role of the host immune response in N. caninum infection and to exploring the immune functions that influence control of infection and disease development ( 7 ). Host immune response against N. caninum infection is an essential determinant of neosporosis ( 1 , 6 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the clinical manifestations of acute toxoplasmosis are partially mediated by an overproduction of the patient’s pro-inflammatory cytokines, e.g. tumor necrosis factor alpha (TNF-α), interleukin-1 (IL-1) and interferon gamma (IFN-γ) [ 6 ], all of which are important in limiting the parasite’s growth [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that SAG1 is able to activate IL‐12 on APCs of both healthy and infected patients. This fact is a relevant for the design of therapeutic strategies (preventive and therapeutic vaccines), considering that this cytokine promotes Th1 polarization, which is involved in the control of T. gondii …”
Section: Discussionmentioning
confidence: 99%
“…The presence of IL‐12 and IFN‐γ is involved in the control of T. gondii infection . In contrast, a shift in bias towards a humoral Th2 immune response is associated with recrudescence of infection and uncontrolled parasite replication . Murine T lymphocytes, in the presence of SAG, produce IFN‐γ and IL‐12 and promote protection against challenge with a T. gondii .…”
Section: Discussionmentioning
confidence: 99%